Interfaith Engagement and the Public Square A Self-Critical Review and Suggestions for the Way Forward (Keynote Address) - Mattson, Ingrid (Journal of the Council for Research on Religion)

(untitled) (Council for Research on Religion, 2023)
A personal and critical essay written by a Muslim religious leader and scholar about the changes they have experienced and witnessed in the ways interfaith dialogue intersects with the public square. The author draws upon twenty-five years of experience, highlighting specific examples affecting the Muslim community, mostly in the United States. The author argues that interfaith dialogue can create space for engagement on issues of public policy and common concern, but that no encounter is ever naïve, and since digital and social media have facilitated the spread of misinformation, such encounters are more complex than before. Further, research on the disproportionate attention negative displays of emotion attract puts minority groups, typically stereotyped as angry and irrational, in a difficult position to express themselves authentically as they try to defend their rights and dignity. Principled interfaith engagement can achieve effective policy results and provide vital moral support to a beleaguered faith community and may create a principled foundation for engagement on other issues. However, this is not always the case, and various parties might express disappointment, even betrayal when “the other side” does not show up for their cause. Nevertheless, continued engagement that allows politically misaligned interfaith partners to express their views according to terms they consider authentic helps avoid greater polarization that is corrosive to social cohesion. At the same time, conveners of interfaith dialogue should be attentive to the structures of power embedded in the programs they create to avoid reinforcing patterns of hierarchy and exclusion.